Language Choice and Participation in Online EMI: Bilingual Practices and Perceptions at a Private Indonesian University - Sri Lestari; Dwi Rosita Sari; Annabelle Bautista Fransisco (VELES Voices of English Language Education Society, 2025)
English-medium instruction (EMI) is expanding in Indonesia through International Credit Transfer (ICT) initiatives, yet its online functioning during early internationalization remains underexplored. This study mapped lecturers’ classroom language practices and examined the attitudes of both lecturers and students toward those practices in online EMI. Using an explanatory case study, we analyzed 30 recorded lessons (five per lecturer), classroom observations, a 5-point Likert survey, and a lecturer focus group, applying content, descriptive, and thematic analyses. Lesson transcripts were coded into five language categories: English only; English–Bahasa Indonesia; English–Bahasa Indonesia–Tagalog; Bahasa Indonesia only; and Bahasa Indonesia–English. Participants included six lecturers and 141 undergraduates across six online courses (Primary Education, Biology, Accounting, Information Systems, Law) at a private Indonesian university implementing ICT in 2023–2024. Overall, English predominated: three lecturers delivered ≥95% English (L1 95.70%; L2 99.88%; L5 98.16%), while two used English–Indonesian code-mixing in about one-fifth to one-quarter of utterances (L4 21.11%; L6 22.80%). One lecturer occasionally incorporated Tagalog alongside English and Indonesian in mixed cohorts. Bilingual strategies clarified key terms and checked comprehension; however, heavy reliance on slides, with limited verbal elaboration, coincided with lower participation. About 50% of students rated EMI positively, 75% needed additional processing to understand the content, and roughly 50% reported difficulty participating in discussions. Findings support a move from English-only to intentionally designed bilingual pedagogy: targeted language-for-teaching professional development (explicit vocabulary scaffolding, multimodal explanations, interaction design, pacing, and turn-taking) and meso-level policies that legitimize judicious use of L1 in online EMI.